Family Business Survival and the Role of Boards. (30th September 2013) - Wilson, Nick; Wright, Mike; Scholes, Louise
Abstract : We explore the vexing question of whether family firms are more likely to survive than nonfamily firms, focusing on the role of board composition. Utilizing a unique data set of over 700, 000 private family and nonfamily firms in the U.K. during 2007–2010, we find that family firms are significantly less likely to fail than nonfamily firms. We identify the board characteristics associated with survival/failure in all firms and determine that it is these characteristics that are important in explaining the lower failure probability of family firms. We conclude with an agenda for further research on boards and family firm survival.